The realization of victims' rights to reparations : assessing the need for a comprehensive reparations program in Uganda - Tindifa, S. (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Prof S. Tindifa, Human Rights and Peace Centre (HURIPEC), Faculty of Law, Makerere University, Uganda.